HUBUNGAN TINGKAT PENDIDIKAN IBU DENGAN PEMBERIAN ASI EKSLUSIF PADA BAYI USIA 7-12 BULAN DI DESA CEPOKO PUSKESMAS SUMBER KABUPATEN PROBOLINGGO: The Correlation between Mother's Education Level and Exclusive Breastfeeding for Infants Aged 7-12 Months in Cepoko Village, Sumber Health Center, Probolinggo - Ekasuma Helyaning Pratiwi; Wahida Yuliana; Nova Hikmawati (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
Exclusive breastfeeding is giving only breast milk without giving other food and drinks to babies from birth to 6 months old, except for medicines and vitamins. The purpose of this study was to find out whether there is a Correlation between the education level of the mother and the provision of exclusive breastfeeding for babies aged 7-12 months in Cepoko Village, the Sumber Health Center, Probolinggo. Quantitative research design with a correlational design using a cross-sectional study approach. The data collection technique used was a checklist sheet with 35 respondents using the Purposive Sampling technique. Data collection includes coding, editing and tabulating, then analyzed manually and by computer with the Chi-Square Test. Research results in 35 respondents Most of the mother's education level, namely secondary education level by 21 respondents (60%) and exclusive breastfeeding for infants aged 7-12 months complete by 26 respondents (73.4%) obtained P Value: 0.000 and α: 0 .05, meaning that H0 is rejected and H1 is accepted so that there is a Correlation between the education level of the mother and the provision of exclusive breastfeeding for infants aged 7-12 months in Cepoko village, Sumber Health Center, Probolinggo. It is hoped that the level of education for mothers with exclusive breastfeeding for infants aged 7- 12 Months in Cepoko village, Sumber Health Center, Probolinggo. Which can increase complete exclusive breastfeeding for infants.